2008
DOI: 10.1007/s10567-008-0032-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Child and Adolescent Pragmatic Language Competencies: Toward Evidence-Based Assessments

Abstract: Using language appropriately and effectively in social contexts requires pragmatic language competencies (PLCs). Increasingly, deficits in PLCs are linked to child and adolescent disorders, including autism spectrum, externalizing, and internalizing disorders. As the role of PLCs expands in diagnosis and treatment of developmental psychopathology, psychologists and educators will need to appraise and select clinical and research PLC instruments for use in assessments and/or studies. To assist in this appraisal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 79 publications
0
35
0
Order By: Relevance
“…Further, in the EPI group, children with a pragmatic deficit had lower IQ's than those with a pragmatic composite score above the cut‐off, t (28) = 2.102, p < 0.05. Due to the explorative nature of these additional analyses, we did not apply Bonferroni corrections (Rothman 1990). Moreover, all seven children with a pragmatic deficit suffered from complex partial seizures.…”
Section: Resultsmentioning
confidence: 99%
“…Further, in the EPI group, children with a pragmatic deficit had lower IQ's than those with a pragmatic composite score above the cut‐off, t (28) = 2.102, p < 0.05. Due to the explorative nature of these additional analyses, we did not apply Bonferroni corrections (Rothman 1990). Moreover, all seven children with a pragmatic deficit suffered from complex partial seizures.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, pragmatic languag-the socially-oriented elements of language use-is thought to be universally impaired in ASD [Kim et al, 2014;Klin et al, 2005;Landa, 2000;Lord and Paul, 1997;Tager-Flusberg et al, 2005;Volden et al, 2009]. Yet, there is little consensus on how pragmatic language abilities should be defined or quantified [Russell and Grizzle, 2008;Volden and Phillips, 2010]. More generally, speech communication is critical for everyday functioning, so there is great potential value for interventions that might increase the capacity of an individual with ASD to understand and be understood [Klin et al, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…These skills contribute to children's psychosocial adjustment and academic achievement (Ervin-Tripp, 1978; McKown, 2007; Coplan and Weeks, 2009; Brinkman et al, 2013). Russell and Grizzle (2008) examined 24 instruments used to assess PS among children and adolescents in order to identify the core domains of PS. They found just over 1000 different items in these instruments, which they grouped into 17 domains and further classified into three sets: (1) Precursors/enablers (e.g., non-verbal communication; discourse attentiveness and empathy; speech characteristics and fluency), (2) Basic exchanges/rounds (e.g., conversational turn taking; topic control and maintenance; requests), (3) Extended literal and non-literal discourse (e.g., negotiations, directions, and instructions; theory of mind; narrative; Gricean principles) (Russell and Grizzle, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Although this classification is helpful, there is still no empirical finding corroborating such a categorization. In fact, Russell and Grizzle (2008) reported that almost none of the authors who constructed the instruments they inventoried had performed factorial analyses. Thus, in order to describe the empirical dimension of PS, specifically among preschoolers, the authors of the present study carried out a systematic literature review and performed a factor analysis (Blain-Brière et al, submitted).…”
Section: Introductionmentioning
confidence: 99%